Manhaj Muqtarah Li`Ta`lim At – Ta`birat Al-Istilahiyah Min Mu`jam At – Tabir Al – Istilahiy Fii Al-Arabiyah Al-Mu`asiroh Lil Duktur Muhammad Muhammad Dawud Li Tullab As – Syanawiyah Al - Faslu Al - `Asir Fii Ma`had Albinaa Bekasi ( Harfu Al – Gha` Hatta - Farhan Lasandi, Naufal; Kholiq Hasan, Moh.Abdul; Qosim, Muhammad Nanang (Ukazh: Journal of Arabic Studies, 2024)
إن التعبير الاصطلاحي هو تعبيرات لا تفهم معانيها من المعاني المستقلة لكل كلمة فيها لأن لها معنى يختلف عنها ولا تفهم معانيها أما معجميا أوتركيبيا. بحيث إن بعض الطلاب وجدوا الصعوبة في الكلام والمعنى اليومية.لذا، إن هذه الدراسة تهدف إلى الكشف والتيسير لمتعلمي اللغة العربية معرفة التعبيرات الاصطلاحية في معجم التعبير الاصطلاحي في العربية المعاصرة للدكتور محمد محمد داود وإعانتهم في اختيار أكثر التعبيرات عونا لهم عند الكلام والكتابة أو القراءة والاستماع. ونهج الباحث على المنهج الوصفي التحليلي في إنجاز هذه الدراسة، وذلك بتتبع التعبيرات الاصطلاحية الموجودة في معجم التعبير الاصطلاحي في العربية المعاصرة للدكتور محمد محمد داود.أثبتت الدراسة على وجود التعبيرات الاصطلاحية في معجم التعبير الاصطلاحي في العربية المعاصرة للدكتور محمد محمد داود، وقد تم العثور على 199 تعبيرا. وكذلك قد جعل الطرق المقترحة لتطبيق منها في إثراء لغة الطلاب، وهي بجعلها على شكل قائمة التعبيرات الاصطلاحية ولكل تعبير بيانها من ناحية لغوية واصطلاحية ووضعها في نص الكتاب وغير ذلك The idiomatic expression is expressions whose meanings are not understood from the independent meanings of each word in them because they have a meaning different from them and do not understand their meanings either lexical or syntactic. So that some students found it difficult to speak and the daily meaning. Therefore, this study aims to reveal and facilitate the learners of the Arabic language to know the idiomatic expressions in the glossary of idiomatic expressions in contemporary Arabic by Dr. Muhammad Muhammad Dawud and to help them choose the most helpful expressions for them when speaking, writing or reading and listening. And the researcher's approach to the descriptive analytical approach to accomplishing this study, by tracking the idiomatic expressions present in the glossary of idiomatic expression in contemporary Arabic by Dr. Muhammad Muhammad Dawud. The study demonstrated the existence of idiomatic expressions in the glossary of idiomatic expression in contemporary Arabic by Dr. Muhammad Muhammad Dawud, and 199 expressions were found. He has also made the proposed methods for applying them to enrich the students ’language, by making them in the form of a list of idiomatic expressions, and for each expression, its linguistic and idiomatic expression and placing it in the text of the book and so on. Idiom istilah termasuk idiom yang tidak mudah dipahami kandungannya yang sesuai di setiap idiom karenanya perubahan makna sendiri tidak bisa dipahami secara seksama dari kata ataupun kalimat. Sehingga para siswa mendapatkan kesulitan dalam menggunakannya dalam percakapan sehari-hari. Tujuan kajian ini untuk mempermudah pelajar bahasa arab dalam mengetahui istilah-istilah dalam kamus muhammad muhammad daud dan membantu mereka dalam memilih kosakata ketika berbicara, menulis, membaca, dan mendengarkan. Adapun kajian ini menggunakan metode analisis-deskriptif, yaitu dengan menelusuri istilah-istilah dalam kamus ini. Penelitian ini membuktikan adanya idiom istilah dalam kamus muhammad muhammad daud. Adapun idiom istilah tersebut mencapai 199 idiom. Penelitian ini juga merumuskan cara-cara yang efektif dalam memperkaya bahasa mahasiswa STIBA Ar-royyah sukabumi, yaitu dengan cara menjelaskan setiap idiom istilah secara etimologi dan terminologi, serta menyajikannya dalam bentuk percakapan sehari-hari dan karya tulis.